2013
DOI: 10.2214/ajr.13.10532
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Imaging–Guided Radiofrequency Ablation for Hepatocellular Carcinomas Not Visible on Conventional Ultrasound

Abstract: Fusion imaging can improve the conspicuity of HCCs and the feasibility of percutaneous RFA of HCCs not visible on conventional ultrasound. Peritumoral anatomic landmarks can be used for electrode placement in HCCs that are still not visible even after image fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 26 publications
4
86
2
Order By: Relevance
“…After the two images match well, the target lesion on ultrasound image can be located according to the CT/MRI image. Previous studies [21][22][23] reported that ultrasound-CECT/CEMRI image fusion technique could detect more tumours than conventional ultrasound (53.3-98% vs 38.8-66%), and it facilitates RFA for liver tumours with poor conspicuity on conventional ultrasound. 17,[24][25][26] However, even with the help of ultrasound-CECT/CEMRI fusion, some lesions still show suboptimal conspicuity on the images of conventional ultrasound, and CEUS is often necessary to confirm the exact location and configuration of the target lesion.…”
Section: Introductionmentioning
confidence: 99%
“…After the two images match well, the target lesion on ultrasound image can be located according to the CT/MRI image. Previous studies [21][22][23] reported that ultrasound-CECT/CEMRI image fusion technique could detect more tumours than conventional ultrasound (53.3-98% vs 38.8-66%), and it facilitates RFA for liver tumours with poor conspicuity on conventional ultrasound. 17,[24][25][26] However, even with the help of ultrasound-CECT/CEMRI fusion, some lesions still show suboptimal conspicuity on the images of conventional ultrasound, and CEUS is often necessary to confirm the exact location and configuration of the target lesion.…”
Section: Introductionmentioning
confidence: 99%
“…There are some new techniques to overcome the limitation of B-mode US-guided RFA (22)(23)(24)(25)(26)(27)(28)(29). One of the new techniques is fusion imaging-guided RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Applying this technique to tumor ablation enhances the identification of target lesions and the feasibility of the intervention [36,37]. In addition, fusion imaging is more useful for RFA in patients with small HCCs because the detectability of HCCs in planning US for RFA depends on the index tumor size [38].…”
Section: Fusing Imaging System For Interventionmentioning
confidence: 99%